2020
DOI: 10.1088/1755-1315/419/1/012147
|View full text |Cite
|
Sign up to set email alerts
|

Integration conceptual framework of quality management system - occupational safety and health- and environment (QHSE) at PT. Wijaya Karya

Abstract: This research is to identify the advantages of integrating quality management systems, Occupational Health and Safety management systems, and Environmental management systems (QHSE Management System). The study was conducted at a State-Owned Enterprises Enterprise. The study will compare All Management Systems with Existing in Wijaya Karya Company with ISO 9001 System on quality management system, ISO 45001 on Health and Safety management system, and ISO 14001 on Environmental management system. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, training given after intervention studies proved significant in increasing the safety of employees. Laksana et al (2020) concluded that the elements of occupational safety system include scope, leadership, policy, planning, support, operations, performance evaluation, and improvement.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, training given after intervention studies proved significant in increasing the safety of employees. Laksana et al (2020) concluded that the elements of occupational safety system include scope, leadership, policy, planning, support, operations, performance evaluation, and improvement.…”
Section: Othersmentioning
confidence: 99%
“…Some past studies have examined the effect of occupational safety on its outcome while studies of its impact on individual employee outcome is rather limited (Qayoom and Hadikusumo 2019;Zhang et al 2019). In addition, there are a few studies that have reviewed the literature to elucidate the status of occupational safety and the outcome of its implementation in the workplace (Laksana et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The standard requires that the top management should ensure during the implementation of the health and safety policy that employees and their representatives are consulted and informed about all aspects of health and safety related to their work. In the process of communication, the institution should also take into account the involvement of workers in consultations concerning OHS activities conducted with them or their representatives, in particular: programmes and procedures for conducting audits, identifying hazards and assessing occupational risks, investigating all incidents (accidents at work, occupational diseases, and potential accidental events), agreeing on an OHS policy along with the organisation's commitment to raise qualifications, and taking into account the role of employees and their involvement in OHS actions (He-ras-Saizarbitoria et al, 2020;Laksana et al, 2020;Uhrenholdt Madsen et al, 2020).…”
Section: The Conceptual and Theoretical Model Of Employee Participati...mentioning
confidence: 99%